Examination of injection moulded thermoplastic maize starch (eXPRESS Polymer Letters)
This paper focuses on the effect of the different injection moulding parameters and storing methods on injection moulded thermoplastic maize starch (TPS). The glycerol and water plasticized starch was processed in a twin screw extruder and then with an injection moulding machine to produce TPS dumbbell specimens. Different injection moulding set-ups and storing conditions were used to analyse the effects on the properties of thermoplastic starch. Investigated parameters were injection moulding pressure, holding pressure, and for the storage: storage at 50% relative humidity, and under ambient conditions. After processing the mechanical and shrinkage properties of the manufactured TPS were determined as a function of the ageing time. While conditioning, the characteristics of the TPS changed from a soft material to a rigid material. Although this main behaviour remained, the different injection moulding parameters changed the characteristics of TPS. Scanning electron microscope observations revealed the changes in the material on ageing.